The Steps of Designing and Compiling a Questionnaire: Dos and Don’ts during Questionnaire Development - Samadi, Assadullah (Journal of Natural Sciences – Kabul University, 2024)
Different tools are available for collecting research data, the most important of which is the questionnaire. Questionnaire design is both an art and a science. Questionnaire researches are widely used in both natural sciences and social sciences. Various factors affect the quantity and quality of the data collected by the questionnaire, the most important of which are validity, reliability, pilot testing and questionnaire format. Although the use of previously validated and published questionnaires is always recommended, in most cases, researchers must design and develop new questionnaires. This new questionnaire should be valid, reliable, clear, concise and interesting in order to collect reliable data and to have a high response rate. In this review article, all stages of designing, development and validation, its benefits and shortcomings of questionnaire are discussed.